ANALISA LAPORAN KEUANGAN SEBAGAI ALAT MENGANALISIS PERKEMBANGAN USAHA DAN PENGAMBILAN KEPUTUSAN PADA CV. MAHARANI PULAU SAMBU GUNTUNG – INDRAGIRI HILIR - Badewin Badewin (JURNAL AKUNTANSI DAN KEUANGAN, 2012)
As for the purpose of this study was to provide imformasi concerning the financial position, the company's performance in terms of liquidity, current ratio and increased efforts to obtain ratings on the incame company. Analisis CV. Maharani in a liquid state where the company is able to pay all liabilities in the form of payment because it has greater assets than debts smooth. In order of writing this paper, the authors used data types perimer and types of secondary data, the authors used data collection methods and a list pertayaan interview. and data analysis using the method of question and answer with employees at the company's accountingdepartments. Liquidity ratio is a measurement tool to know the company's ability to meet its short term obligations that must be met in time to pay its obligations, from table 1.1 income statement as of 31 December 2007 and in 2008 net income 485 945 000, - and 532 920 000, - meaning that there is an increase in revenue and accompanied by other items so that the net income derived did not experience a significant increase, the company also sought to curb expenses or costs, so profits become larger than the previous year.